Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s13632-018-0427-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of New Ti–Al–Fe–Cr Transition Class Alloy Produced by Blended Elemental Powder Metallurgy Using TiH2 and Master Alloy

Abstract: Blended elemental powder metallurgy using titanium hydride and Al-Fe-Cr master alloy powders was employed to produce a new Ti-1.5Al-1Fe-7.2Cr (wt.%) transition a ? b/b metastable-type alloy. A simple process involving blending, cold pressing, and sintering resulted in a material with a residual porosity of not higher than 3.9-5%, a uniform and relatively fine-grained microstructure (average b-grain size of less than 100 lm), and acceptable mechanical properties. The influence of subsequent annealing and hot pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…2b). The regimes of subsequent thermomechanical processing and heat treatments were chosen basing on the technological approaches developed in [16,[22][23][24]. Machined semiproducts were subjected to 3D pressing at initial temperature of 1100 °C (Fig.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…2b). The regimes of subsequent thermomechanical processing and heat treatments were chosen basing on the technological approaches developed in [16,[22][23][24]. Machined semiproducts were subjected to 3D pressing at initial temperature of 1100 °C (Fig.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…The results of tensile tests of all program materials are presented in Table 5. Data for the Ti-1.5Al-1Fe-7.2Cr alloy (lines 17-19) with somewhat higher chromium content [23,24] were added for comparison to illustrate the influence of C Mo above 10 wt.%. Typical examples of engineering tensile stress-strain curves for alloys #3 and #4 are given in Fig.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even this as-cast state could be employed for further study regarding the influence of isothermal exposure on the aging behaviour. However, taking into account previous data obtained with a similar composition alloy obtained by the elemental powder metallurgy approach [10], and keeping in mind the aim to eliminate the possible influence of structural and chemical inhomogeneity of the initial cast state, water quenching was applied after exposure at 1173 K for 3.6 ks (single-phase β-field) to form and retain a uniform single-phase metastable β-state. The water quenched specimens were then subjected to isothermal exposure for various durations at two temperatures of 673 and 773 K to study the aging behaviour.…”
Section: As-cast State and Aging Behaviour Of Solution-treated And Quenched Alloymentioning
confidence: 99%
“…Another successful approach has been to produce low-cost Ti-Al-Fe-Cr alloys containing high amounts of relatively cheap Fe and Cr [8,9]; however, all developed compositions to date have corresponded to the higher-alloyed metastable β-alloy type. In our previous work [10], where an elemental powder metallurgy approach was employed, we showed that the composition of an alloy of this type can be changed to a lower content of β-stabilizing elements, such as iron and chromium, to 1 and 7% mass, respectively, which corresponds to a molybdenum equivalent of C Mo = 11.5% mass. Such a reduction in the content of β-stabilizing elements allows both a reduction in the cost and specific weight of the alloy, in addition to simplification of the smelting process (due to faster melt homogenization) and shortening of the isothermal exposure during heat treatments due to the high diffusibility of Cr and especially Fe.…”
Section: Introductionmentioning
confidence: 98%